Development of an Interactive E-Module Based on Inquiry Learning for Calculus Derivative Topics in Higher Education - Lilla Puji Lestari; Gregorio Antonny Bani; Raveenthiran Vivekanantharasa (International Journal of Mathematics and Science Education, 2024)
This research investigates the development and testing of an interactive e-module based on inquiry learning, designed to improve students’ understanding of derivatives in calculus. The study adopts a Research and Development (R&D) approach, which involves several stages: design, prototype creation, testing, and revision. The e-module incorporates interactive exercises, real-time feedback, and multimedia elements to engage students in active learning. A pre- and post-test assessment was conducted to measure the effectiveness of the e-module, revealing a 20% improvement in students’ conceptual understanding of derivatives. Feedback from students indicated that the e-module’s interactive features, including visual representations, problem-solving activities, and immediate corrections, significantly enhanced their learning experience. The results were compared with traditional printed materials, showing that the interactive e-module was more effective in improving students' problem-solving skills and overall understanding of abstract concepts in calculus. The findings suggest that technology-enhanced tools, such as interactive e-modules, offer a promising approach to calculus education, fostering deeper engagement and providing immediate feedback, which traditional methods fail to offer. These tools are particularly beneficial in bridging the gap between theoretical understanding and practical application in higher education. The study also recommends expanding the use of inquiry-based learning and interactive modules to other areas of mathematics and STEM education. Future research should focus on refining the e-module to include more personalized learning pathways and explore its long-term effects on students' performance across various subjects.